SOCIAL LIFE OF THE MALAY COASTAL COMMUNITY OF PANTAI CERMIN - Nafisa Fadhilah Bahri; Aprilli Khosyi Nasution; Rahmad Muliadi; M.Zhafran Afif Hayri; Miftahul Fauzan (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
Coastal communities play an important role in food provision, especially marine products such as various types of fish consumed by the wider community. The vastness of Indonesia's waters means that the country has coastal communities whose livelihoods are highly dependent on marine resources. Living in direct contact with the sea shapes the unique socioeconomic characteristics of coastal communities. This article discusses the social life of coastal communities, particularly the social structure that encompasses various levels, from fishing leaders, bosses or middlemen, fishermen who also own boats, to fishing laborers. The coastal community in Karangantu has distinctive characteristics such as a strong identity, consisting of various ethnic groups but with uniform economic activities, high population density, and limitations in meeting their daily needs. The factors that influence their economic conditions include natural conditions, the availability of facilities and infrastructure, access to capital, government policies, and market price fluctuations.